Phytochemical and Nutritional Composition of Vernonia Amygdalina: Antioxidant, Antidiabetic Efficacy, and Hematological Benefits - Adewuyi, Hassan Abdulsalam (Pharmacology and Clinical Pharmacy Research, 2025)
Vernonia amygdalina, a traditionally used medicinal plant, has been purported to possess health-promoting properties.The aim of this study is to investigate the phytochemical and nutritional composition of V. amygdalina, evaluate its antioxidant and antidiabetic efficacy, and assess its hematological benefits. Phytochemical screening, proximate analysis, antioxidant assays (DPPH, ABTS), antidiabetic evaluations in streptozotocin-induced diabetic rats, and hematological assessments were conducted according to standard protocol. V. amygdalina exhibited a rich phytochemical profile, comprising flavonoids, phenolic acids, and terpenoids, alongside significant antioxidant activity (IC50 = 12.5 μg/mL) and complete source of protein. Proximate analysis revealed high protein (21.1%) and fiber (15.6%) content. Antidiabetic evaluations demonstrated significant reductions in blood glucose levels (p < 0.01). Hematological assessments showed significant improvements in hemoglobin (14.1 ± 0.6 g/dL), packed cell volume (42.9 ± 1.8%), red blood cell count (7.1 ± 0.3 x 10^12/L), and differential WBC count, including reduced monocyte (6.3 ± 0.9%) and eosinophil (2.6 ± 0.6%) percentages, and increased lymphocyte (34.4 ± 2.4%) percentage. This study provides comprehensive evidence for the phytochemical, nutritional, and pharmacological value of V. amygdalina, underscoring its potential as a functional food and phytomedicine for oxidative stress and diabetes management, as well as a natural adjunct for improving hematological parameters.